Data on thermostable β-glucosidase immobilized by Zn2+ - Xuejia Shi; Linguo Zhao; Jianjun Pei; Lin Ge; Pengwei Wan; Zhenzhong Wang; Wei Xiao (Data in Brief, 2018)
In this article, the methods for detection of enzyme activity and protein concentration are described. The data of the calibration curves can be used for a further understanding on the assays of enzyme activity measured with p-nitrophenyl-β-D-glucopyranoside (pNPG) or cellobiose as the substrate. In addition, the data presented provides an analytic method for measuring protein concentration in mixed samples.